KONSEP DESIGN CATALYST DALAM REVITALISASI KAWASAN Studi Kasus Penataan Kawasan Kota Agung Kabupaten Tanggamus - Agung Cahyo Nugroho (UNIVERSITAS LAMPUNG, 2011)
Phisycal intervention in the planning process could be the ‘micro’ intervention, which mean thatthe pysical aspect of infilltration is the growth ‘catalyst’ of the area/environment. Catalyst is oneof the concept for revitalitation strategy in built area/environment. In the concept of urbancatalyst, architectural design could be the catalyst for area/environment planning and designingprocess. This concept give important point for revitalitation process, which mean ‘designarchitectural’ could be the catalyst for revitalitation. Kota Agung as the municipal of KabupatenTanggamus has a significant history as one of important place in South of Sumatra in colonialismera, which is also indicate by its location. This study take as design study with synoptic method asthe metodology of the study. From the analysis process, showed that public space, commercialcenter and beach/waterfront activity could be the catalyst for the growth of Kota Agung. Thisprocess also could reinforce the cultural aspect of the place. Those catalyst could be moresignificant with the forming of linkage system in the area/environment.